The Role of Media in Socialization to Reduce the Phenomenon of Street Children: A Field Study on Tikrit University Students (Journal of Al-farahidi's Arts, 2026)
The media has contributed to stimulating the socialization process by influencing people's behavior and attitudes. It is not limited to merely transmitting news and information; it is also an effective tool for educating and guiding the public. From this standpoint, the media has played a significant role in strengthening community ties and influencing public opinion, demonstrating its importance in maintaining social order and encouraging development. This contribution begins in early childhood, as the media provides educational and entertainment programs that enhance attention, awareness, and behavioral growth, complementing parents' efforts to shape values and guide attitudes. This study explores the role the media aspires to play in promoting the socialization process and the extent to which this role can mitigate the phenomenon of street children, a growing social problem in developing countries, including Iraq. Tikrit University students were selected as the sample for the field study, as they represent a well-educated youth segment that interacts daily with the media and its behavioral and cultural influences. The study relied on a descriptive analytical approach, and a questionnaire was used as the primary tool for collecting data from the student sample